Access to OUD Treatment and Maintenance of Sobriety amid the COVID-19 Pandemic. (7th June 2021) - Rahman, Fatima; Evans, NaKiera; Bernhardt, Jean
Abstract: Objectives: The COVID-19 pandemic changed the way that healthcare is delivered, with non-urgent care becoming almost entirely virtual. Underserved communities already battling the opioid epidemic had new challenges in accessing medication assisted treatment (MAT). The investigators sought to determine if patients were retaining access to their opioid use disorder (OUD) treatment and maintaining sobriety during the pandemic, with the intention of using this information to improve subsequent patient care while the pandemic continues. Methods: In the assessment, seventy-five patient Epic EMR (electronic medical record) charts were reviewed to collect information on demographics, socioeconomic factors, healthcare access and sobriety during the pandemic period between March 1 st, 2020 and June 15 th, 2020. Patient charts were selected based on those receiving office-based opioid treatment (OBOT) for OUD at an urban healthcare center. Results: 98.7% of patients accessed the healthcare center in some form since March 1st, 2020. The most common form of communication was through telemedicine with 94.6% of calls over audio. Out of the 21 toxicology screens performed during the pandemic period, 16 (76%) patients were found to be adhering to their buprenorphine treatment. Only 78.7% had documented they had Narcan at their disposal. Among all patients, 11 (14.6%) reoccurrences in opioid use were documented during the pandemic period. Few patients (76%) were adhering to their prescribed buprenorphine treatment, revealing that patients may not be receiving needed MAT support amid the pandemic. Conclusion: This assessment reveals short-comings of patient education in managing craving and the maintenance of support systems amid social-isolating conditions.